2012
DOI: 10.1137/090757125
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Sampling for Linear State Estimation

Abstract: When a sensor has continuous measurements but sends limited messages over a data network to a supervisor which estimates the state, the available packet rate fixes the achievable quality of state estimation. When such rate limits turn stringent, the sensor's messaging policy should be designed anew. What are the good causal messaging policies ? What should message packets contain ? What is the lowest possible distortion in a causal estimate at the supervisor ? Is Delta sampling better than periodic sampling ? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
106
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 26 publications
4
106
1
Order By: Relevance
“…Event-triggered sampling is also referred to as adaptive sampling in Rabi et al [2012], Lebesgue sampling inÅström and Bernhardsson [2002] and dead-band control in Otanez et al [2002], Hirche et al [2005]. The event-trigger is a preprocessing unit situated at the sensor which decides upon its available information, whether to update the estimator with current information.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Event-triggered sampling is also referred to as adaptive sampling in Rabi et al [2012], Lebesgue sampling inÅström and Bernhardsson [2002] and dead-band control in Otanez et al [2002], Hirche et al [2005]. The event-trigger is a preprocessing unit situated at the sensor which decides upon its available information, whether to update the estimator with current information.…”
Section: Introductionmentioning
confidence: 99%
“…Examples for such networked control systems are given by sensor networks, multi-robot systems and distributed power generation networks. The work inÅström and Bernhardsson [2002] and Rabi et al [2012] showed that event-triggered sampling outperforms periodic sampling with respect to the state estimation error of a first-order linear system in the presence of two different communication constraints. In Rabi et al [2012], the communication constraint is induced by limiting the number of transmissions during a finite interval, whereas the work inÅström and Bernhardsson [2002] limits the average transmission rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in practice, often only noisy measurements are accessible. The event-trigger can be obtained by formulating the design as an optimal stochastic control problem [7], [10], [12]. These works show that eventtriggered sampling outperforms time-triggered schemes also in the multiple-loop NCSs.…”
Section: Introductionmentioning
confidence: 94%